The effectiveness of a training program designed according to knowledge management processes in developing academic scientific research skills (A quasi-experimental study on a sample of students from the Department of Curriculum and Teaching Methods at Tishreen University) - الشيخ, ساره; سمر يوسف; نورا محمود (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to reveal the effectiveness of a training program designed according to knowledge management processes (identifying and diagnosing knowledge, generating knowledge, storing knowledge, disseminating knowledge, applying knowledge and using it) in developing academic scientific research skills (the skill of collecting scientific material, the skill of developing previous studies, the skill of identifying... Research sample, the skill of identifying research variables, the skill of defining the research problem, the skill of formulating the research problem, the skill of formulating the research title, the skill of defining research hypotheses, the skill of determining the importance of research, the skill of defining research objectives, the skill of designing research tools (questionnaire), the skill of interpreting results. Research, the skill of submitting research proposals, the skill of developing a research summary. The researcher adopted the quasi-experimental approach and the one-group design (pre- and post-test). The research sample consisted of (17) female students from the Department of Curriculum and Teaching Methods from the Faculty of Education at Tishreen University. The researcher designed two tools to achieve the research goal by measuring the effectiveness of the training program, which are: a cognitive test to measure the cognitive aspect of academic scientific research skills; And a skills test to measure the performance aspect of academic scientific research skills. The results of the research showed the following: The effectiveness of the training program designed according to knowledge management processes in developing academic scientific research skills There is a statistically significant difference at the significance level (0.05) between the average scores of female students in the pre- and post-applications of the cognitive test for scientific research skills as a whole, and for each skill separately. There is a statistically significant difference at the significance level (0.05) between the average scores of female students in the pre- and post-applications of the skills test for scientific research skills as a whole, and for each skill separately.